Neutral and Negatively Charged Phosphate Modifications Altering Thermal Stability, Kinetics of Formation and Monovalent Ion Dependence of DNA G‐Quadruplexes. Issue 8 (24th January 2019) - Su, Yongdong; Fujii, Hirofumi; Burakova, Ekaterina A.; Chelobanov, Boris P.; Fujii, Masayuki; Stetsenko, Dmitry A.; Filichev, Vyacheslav V.
Abstract: The effect of phosphate group modifications on formation and properties of G‐quadruplexes (G4s) has not been investigated in detail. Here, we evaluated the structural, thermodynamic and kinetic properties of the parallel G‐quadruplexes formed by oligodeoxynucleotides d(G4 T), d(TG4 T) and d(TG5 T), in which all phosphates were replaced with N ‐methanesulfonyl (mesyl) phosphoramidate or phosphoryl guanidine groups resulting in either negatively charged or neutral DNA sequences, respectively. We established that all modified sequences were able to form G‐quadruplexes of parallel topology; however, the presence of modifications led to a decrease in thermal stability relative to unmodified G4s. In contrast to negatively charged G4s, assembly of neutral G4 DNA species was faster in the presence of sodium ions than potassium ions, and was independent of the salt concentration used. Formation of mixed G4s composed of both native and neutral G‐rich strands has been detected using native gel electrophoresis, size‐exclusion chromatography and ESI‐MS. In summary, our results indicate that the phosphate modifications studied are compatible with G‐quadruplex formation, which could be used for the design of biologically active compounds. Abstract : Don't be so negative ! In contrast to native negatively charged DNA strands, G‐quadruplex assembly by a charge‐neutral TG4 T sequence in which all phosphates are modified with phosphoryl guanidine groups is faster in Na + than K + ions and independent of the salt concentration used. Charge‐neutral G‐rich sequences can also invade into the pre‐formed native G‐quadruplex DNA.